Forensic Product Examinations in the System of Forensic Institutions of the Russian Ministry of Justice: Current State and Future Prospects - A. A. Selivanov (Теория и практика судебной экспертизы, 2018)
The article presents an overview of expert Product examinations conducted by the Russian Federal Centre of Forensic Science of the Ministry of Justice of Russian Federation over the period 2014–2018. The author considers investigations related to criminal, civil and arbitration cases and nonjudicial investigations carried out at the request of natural and legal persons. Practical recommendations are offered for practitioners dealing with evidence that qualifies for this type of forensic investigation. Casework examples cover a variety of Product groups: clothing and footwear, fabrics, vehicle spare parts and components, gems and non-precious stones, art and antiques, coins, equipment, and weapons. Algorithms are offered for typical tasks that may be completed in the course of a forensic Product investigation in order to establish the following facts: the possibility of placing an item in specified storage conditions; compliance (non-compliance) of actual storage conditions with standards and specifications; the degree of loss in quality and value of an item, taking into account its actual state or period of operation; the market value of equipment leasehold rights. The prospects for developing Product expertise in forensic institutions of the Russian Ministry of Justice are defined.